PERSEPSI GURU PAUD TERHADAP PEMBELAJARAN PARADIGMA BARU MELALUI KURIKULUM MERDEKA - Rosyida Nurul Anwar (AZZAHRA, 2022)
Changes and developments are happening so fast today; we always demand to be ready to adapt to these changes. The education system provides direction and signs in carrying out education. The curriculum is one of the essential organs in fulfilling the order and goals of education. Teachers have a significant and central role in running and achieving a curriculum. A teacher or teacher can carry out and succeed in the teaching and learning process with the applicable curriculum at school. This study aimed to determine the teacher's perception of the new paradigm of learning the Merdeka Curriculum. The research location is in six PAUD institutions that are members of the Motivating School Program in Madiun Regency with as many as 16 teachers. The research uses a descriptive approach with the type of case study—data collection techniques through semi-structured interviews in adoption and focus group discussions. The results of the study indicate that teachers have various perceptions of the Merdeka Curriculum, namely, the teacher views that the Merdeka Curriculum is the needs and interests of students, is dynamic and flexible, and adapted to the needs of the school; The Merdeka Curriculum is a reference for teachers to think more creatively to realize independent learning. The Merdeka Curriculum is more straightforward in making activity plans